A study on the locally high-gradient displacement field resulted from plastic hinges in steel beams. Issue 10 (July 2019) - Xu, Jin; Lee, Chi King; Tan, Kang Hai
In this study, an investigation on the deformation profiles near the plastic hinge regions of propped cantilever beams is carried out by both experiment and numerical simulation. In the experiment, two series of beams are loaded until two plastic hinges are formed at the loading point and the fixed end. In the numerical simulation, the extended finite element method formulation is employed to simulate the non-smooth displacement field resulted from the plastic hinges. The comparison on the experimental and the numerical results shows that the Hermite function is able to describe the non-smooth displacement resulted from plastic hinges in the steel beams.